Comparative reference of accommodation tension in schoolchildren of junior classes depending on emotional state - L. E. Fedorischeva (Oftalʹmologiâ, 2014)
Purpose: to study the change of adaptation mechanisms in children of junior classes during working on close distance depending on their psychoemotional state. Methods: 52 children of the second classes of grammar school were included into the study. There were allocated 30 emotional labile schoolchildren with choleric temperament. The children were examined by pediatrician, neurologist and in laboratory. Standard ophthalmic examination was performed. Accommodation was examined by subjective (reserve of relative accommodation) and objective (familiar tone of accommodation) methods. Results: All children had low reserve of relative accommodation (RRA) and high familiar tone of accommodation (FTA) in the end of educational week especially in emotional labile children. After course of treatment (hygiene of visual activity; restoration of accommodation and therapy of visual tiredness; gymnastics for cervical spine; preparations with microelements, vitamins C,E, B-carotene; fenibute) RRA was increased and FTA was decreased even in emotional labile children. Conclusion: There is correlation between refractive-accommodative apparatus and psychoemotional state in schoolchildren of junior classes.